2010
DOI: 10.1111/j.1865-1682.2010.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza Survey in Migrating Waterfowl in Sonora, Mexico

Abstract: A two-year survey was carried out on the occurrence of avian influenza in migrating birds in two estuaries of the Mexican state of Sonora, which is located within the Pacific flyway. Cloacal and oropharyngeal swabs were collected from 1262 birds, including 20 aquatic bird species from the Moroncarit and Tobari estuaries in Sonora, Mexico. Samples were tested for type A influenza (M), H5 Eurasian and North American subtypes (H5EA and H5NA respectively) and the H7 North American subtype (H7NA). Gene detection wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…One of the findings in this study was the detection of 22 wild dabbling ducks (3.68%) positive to IAV in the mid-winter. The low viral detection observed in the current study was consistent withMontalvo-Corral et al (2011), who reported an overall prevalence of 3.6%, mostly in dabbling ducks from estuaries close to agricultural areas and peri-urban settlements in northern Mexico. Nevertheless, a high prevalence has also been reported among wild waterbirds as 26% in eastern Mexico(Cerda- Armijo et al, 2020).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…One of the findings in this study was the detection of 22 wild dabbling ducks (3.68%) positive to IAV in the mid-winter. The low viral detection observed in the current study was consistent withMontalvo-Corral et al (2011), who reported an overall prevalence of 3.6%, mostly in dabbling ducks from estuaries close to agricultural areas and peri-urban settlements in northern Mexico. Nevertheless, a high prevalence has also been reported among wild waterbirds as 26% in eastern Mexico(Cerda- Armijo et al, 2020).…”
supporting
confidence: 91%
“…The UIFMVZ377/H5N2 was phylogenetically related to North American wild ducks. Influenza prevalence varies from 0.7% in southern U.S. to 55% in northern Canada (Montalvo-Corral et al, 2011). Seasonality, geographical location and between-year fluctuations can modify the IAV prevalence and subtype distribution.…”
Section: Ta B L E 2 Ncbi Genbank Accession Numbers Of Influenzamentioning
confidence: 99%
“…The percentage of positive samples recovered during routine surveillance programmes suggested low infection rates, ranging from 0.07% to 0.62% in Argentina [5254]; 1.19% in Barbados [55]; 0.71% in Brazil [56]; 3.6% in Mexico [41]; and between 0.22% and 0.88% in Peru [44, 57]. However, these results may not represent the actual prevalence rates of avian influenza in the countries analysed.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, LPAI H7N3 viruses were isolated in Mexico in 2009 from wild duck samples ( Anas cyanoptera ) and were phylogenetically linked to North American viruses [40]. Simultaneously, another study reported the circulation of AIVs of the H5, H6, and H9 subtypes, which belong to North American lineages that are very closely related to virus isolates from California in previous years [42], demonstrating the continuous migration of AIVs throughout the avian migration seasons and suggesting the occurrence of AIVs transmission from resident waterfowl to poultry or other domestic animals [41]. …”
Section: Resultsmentioning
confidence: 99%
“…A previous eco-epidemiological study demonstrated IAV circulation in migratory birds in the Northwestern Mexican wetlands and partial characterization of hemagglutinin genes of some viruses was performed; however, at that time we could not isolate and characterize whole samples. (14,15) For this reason, in this study we took advantage of high-throughput generation sequencing, to achieve full characterization and perform in-depth phylogenetic analysis of the whole genome of several IAV sampled from wild birds in the Pacific flyway migratory grounds in Mexico.…”
Section: Introductionmentioning
confidence: 99%